A soberania dos dados versus a autonomia do usuário: Big Data, Internet das Coisas e as estratégias afirmativas do anonimato - Abreu, Giovanna Oliveira Lima de (2015)
The interaction between society and technology in the context of mediated ambience, enhanced by processes and tools such as Big Data and Internet of Things are the basis of scientific advances that are gradually transforming our daily lives. With the Big Data phenomenon we are able to capture a massive quantity of data, creating endless possibilities of connections and control. The Internet of Things, in turn, is related to embedded devices networks that communicate with each other in an automated way to help make our lives more efficient and more vulnerable too. In the era of pervasive computing and datafication, any attempt to safeguard our data seems insufficient. So, this study presents a reflection on the existing oppositeness between the ideas of freedom as an essential attribute for online information sharing and the sovereignty imposed by the data control, besides we also examine the implications of this surveillance on the user autonomy. To understand the links between the mediations, the network and the members of this interconnected system, we adopted the Actor-Network Theory (LATOUR, 2012). This theory of social also inserts itself as the methodology, laying the foundations for guiding this study. Another important point is to understand the conceptual differences between surveillance, control and monitoring (LEMOS, 2009). The work, divided into two parts and their respective chapters, also includes the analysis of some attempts of resistance to this control imposed on members of the interconnected public sphere, and it points out the paradoxes concerning, particularly, to anonymity, one of the main forms of opposition to the monitoring state established in the net. Since we are in the middle of a still in progress process, accurate and airtight conclusions are not possible. However, if we are not able to set limits to the new digital society, then we run a risk of seeing vital rights, essential to the proper functioning of society, wrecked in the name of innovation and convenience.